STUDI EKSPERIMEN PENINGKATAN PERPINDAHAN KALOR FLUIDA NANO CuO /AIR PADA VERTICAL HELICAL MICROFIN TUBE - Kristiawan, Budi; Khoirudin , Ilham; Wijayanta, Agung Tri; Hadi , Syamsul; Effendi, Hilbran Tama Dida (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The way to increase heat transfer is to use nanofluids and expand the heat transfer area. This research studied the thermal performance, convection heat change coefficient, and pressure drop in a double pipe heat exchanger experimentally in a vertically arranged helical microfin tube heat exchanger. Hot water flows on the side of the annulus. In contrast, nanofluid CuO/distilled water concentration of 0.05 vol% flows laminarly in the inner pipe of the microfin tube with cross-flow and parallel-flow arrangements. The result is convection heat transfer coefficient enhancement and thermal performance factor compared to the base fluid. Counter flow improves heat transfer better than parallel flow. This research contributes to the use of helical microfin and nanofluids to increase heat transfer in heat exchangers used in industrial processes.